Prispevek k flori, favni in ekologiji Krke v okolici Dobrave (Varstvo narave, 1977)
From the investigated part of the Krka river (Dolenjska, Yugoslavia) there have been treated 103 water plant species and 20 invertebrate categories. Zosteraceous species Potamogeton filiformis has been known in Slovenia only from the Submediterranean. Megalopteran Sialis nigripes and neuropteran Sisyra terminalis are new for Yugoslavia. River plant communities belong to the associations Potameto perfoliati-Ranunculetum fluitantis and Ceratophylletum demersi. Among plants quantitatively prevail higher-plant genera Ranunculus, Myriophyllum and Potamogeton. Among animals dominate Gastropoda, Amphipoda, Diptera, Ephemeroptera and Trichoptera. Travertine formation is supported indirectly by macrophyta, and directly by Cyanophyta, snails, shells and trichopterous and chironomid larvae. Polution, determined by indicators-species, is within the category of middle pollution, i.e. beta mesosaprobic class.
Keywords: biologija; biology